2021
DOI: 10.1186/s12885-021-07798-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of breast cancer among patients in a tertiary care hospitals in Afghanistan: a case control study

Abstract: Background Breast cancer is the second most common causes of women’s death, worldwide. Data on risk factors associated with female breast cancer in the Afghan population is very limited. The aim of our study was to identifying risk factor associated with female breast cancer in Afghanistan. Methods A retrospective case-control study was conducted with inclusion of 201 cases and 201 controls. Patient information was collected by interviewing the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In these areas, patients suffer from poor hygiene, poor transport facilities to health centres and limited medical knowledge in self-assessment [ 3 6 ]. There are only sparse data on breast cancer in Afghanistan [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, patients suffer from poor hygiene, poor transport facilities to health centres and limited medical knowledge in self-assessment [ 3 6 ]. There are only sparse data on breast cancer in Afghanistan [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in our participants, there was no association between BC and other factors like smoking and HRT. A similar study found no statistically significant association between smoking and the risk of BC [50] .…”
Section: Discussionmentioning
confidence: 84%
“…Our results confirmed this hypothesis since those subjects who had breastfed for longer than 3 months and who had no family history of breast cancer were diagnosed with breast cancer at a more advanced age. Nevertheless, it is also true that despite existing evidence on the protection afforded by maternal lactation against breast cancer, some studies show no clear effects of breastfeeding on breast cancer incidence (Alsolami et al, 2019; Baset et al, 2021). For this reason, more in-depth studies and larger population samples are needed in order to investigate and possibly confirm the potential influence of factors, such as obesity or breastfeeding in the development of female breast cancer.…”
Section: Discussionmentioning
confidence: 99%